Pelatihan Penggunaan Smartphone dan Aplikasi Komunikasi Digital untuk Peningkatan Kompetensi Lansia - Yudhistira Arie Wijaya; Riri Narasati; Mifta Almaripat; Mita Amelia (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Advances in digital technology have had a significant impact in various aspects of life, including for the elderly. However, limited digital knowledge and skills cause many elderly people to not be able to utilize technology optimally. This community service activity aims to improve the digital competence of the elderly through training on the use of smartphones and daily communication applications such as WhatsApp and Google Meet. The methods used include a participatory approach, direct assistance, and repeated practice of using digital applications in a friendly and fun atmosphere. The activity was carried out at Posyandu Lansia Kelurahan Jatimakmur, Bekasi, involving 30 elderly participants aged 60-75 years. The results of the activity showed a significant improvement in the participants' ability to use smartphones, access communication applications, and understand digital communication ethics. Evaluation was conducted through pre-test and post-test, as well as direct observation during the training. The majority of participants stated that they felt more confident and motivated to continue learning to use technology. Supporting factors for the success of this activity included the personal approach, the patience of the facilitators, and the use of visual and practical methods. Meanwhile, the challenges faced included participants' physical limitations, such as visual and hearing impairments, and memory limitations. This activity makes a real contribution to the digital empowerment efforts of the elderly, and opens up opportunities for the development of similar programs in other regions. Hopefully, this kind of training can be the first step towards comprehensive digital inclusion for all levels of society.